Identification And Synoptic Analysis Of The Types Of Weather In The City Of Ahar - KARIM AMININIA; Ali Mahmoudei (نشریه جغرافیا و برنامه‌ریزی, 2019)
One of the things done in the field of synoptic climatology is air typology. An air typology represents types of air that are similar enough in terms of particular atmospheric variables. The emergence of an air type in a certain area, on one hand, depends on the air masses entering to the area, and on the other hand, reflects the geographic conditions (roughness, adjacency to the masses of water, etc.) of that area. Since the geographic conditions of each area are usually constant, the difference in air types that come and go in the region is a function of the air masses that enter the area. Characteristics of the air masses while moving and crossing different areas, change, adjust and turn into another air. Given the fact that the repetition of air types determines the climate in an area, it is very important to identify the types of air. This is because without knowing the types of air dominating an area, management and planning will be very difficult and even impossible. This is while by identifying air types, it will possible to identify possible types of natural disasters in different sectors of agriculture, industry, etc. and prevent its damages. Since each type is related to circulation patterns, recognizing the characteristics, severity, and frequency of each type can show us their remaining time and duration of their domination, and help us in planning